Evaluation of sodium hypochlorite as a denture cleanser: a clinical study. (12th December 2013) - de Sousa Porta, Sheila Rodrigues; de Lucena‐Ferreira, Sílvia Carneiro; da Silva, Wander José; Del Bel Cury, Altair Antoninha
Abstract : Objectives: To evaluate the effect of sodium hypochlorite (NaOCl) on biofilms, colour stability (ΔE) and surface roughness (Ra) of complete dentures and patient acceptability. Background: Denture cleansers should be able to reduce the accumulation of biofilms without affecting the acrylic resin properties. Patient satisfaction is important to maintaining their daily use. Materials and methods: Fifteen participants were instructed to keep their dentures immersed daily in a 0.5% NaOCl solution for 3 min over 90 days. Swabs were taken from dentures and inoculated on CHROMagar and blood agar. The number of colony‐forming units (cfu) was counted after a 48‐h incubation period. ΔE was assessed using the CIE L*a*b* system. Ra was measured using a profilometer. Patient acceptability was checked based on their degree of satisfaction. Cell counts, ΔE and Ra were analysed usinganova, Friedman's and Kruskal–Wallis tests, respectively (α = 0.05). Results: A significant reduction in the total number of microorganisms ( p  = 0.001) and Candida spp. was noticed. No significant differences were found for ΔE ( p  = 0.68) and for Ra ( p  = 0.47). The level of the patient satisfaction increased throughout the follow‐up period. Conclusion: The 0.5% NaOCl solution was effective in reducing microorganisms without significant changes in colour or roughness of denture resin. The participants reported satisfaction with the cleaning results.